ISTAC-IIUM Annual Report 2023 - Norman, Nurul Ain (International Institute of Islamic Thought and Civilisation (ISTAC-IIUM), 2024)
2023 Annual Report of International Institute of Islamic Thought and Civilisation (ISTAC-IIUM)